1996
DOI: 10.1128/mcb.16.4.1376
|View full text |Cite
|
Sign up to set email alerts
|

The LIM Domain-Containing Dbm1 GTPase-Activating Protein Is Required for Normal Cellular Morphogenesis in Saccharomyces cerevisiae

Abstract: Normal cell growth in the yeast Saccharomyces cerevisiae involves the selection of genetically determined bud sites where most growth is localized. Previous studies have shown that BEM2, which encodes a GTPaseactivating protein (GAP) that is specific for the Rho-type GTPase Rho1p in vitro, is required for proper bud site selection and bud emergence. We show here that DBM1, which encodes another putative Rho-type GAP with two tandemly arranged cysteine-rich LIM domains, also is needed for proper bud site select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 87 publications
3
43
0
Order By: Relevance
“…6B). When we counted only those cells that had more than two bud scars (that were spaced separately), a significant number of rga1Δ cells exhibited the bipolar pattern (62%, n=50), as previously reported (Chen et al, 1996;Smith et al, 2002;Stevenson et al, 1995). Because bud scars within a bud scar were sometimes less clear from static images (see Fig.…”
Section: Transient Changes In Rga1 Distribution During Cytokinesis Anmentioning
confidence: 84%
See 2 more Smart Citations
“…6B). When we counted only those cells that had more than two bud scars (that were spaced separately), a significant number of rga1Δ cells exhibited the bipolar pattern (62%, n=50), as previously reported (Chen et al, 1996;Smith et al, 2002;Stevenson et al, 1995). Because bud scars within a bud scar were sometimes less clear from static images (see Fig.…”
Section: Transient Changes In Rga1 Distribution During Cytokinesis Anmentioning
confidence: 84%
“…Because Cdc42 GAP(s) are likely to affect the dissociation rate of Cdc42 from the plasma membrane to the cytoplasm, we considered Rga1, which is the only Cdc42 GAP that specifically affects the axial budding pattern (Chen et al, 1996;Smith et al, 2002;Stevenson et al, 1995;Tong et al, 2007). Although it has been shown that Rga1 blocks Cdc42 polarization at the division site (Tong et al, 2007), it is unclear when Rga1 functions relative to the two steps of Cdc42 activation and whether Rga1 activity is involved in the fluctuating levels of Cdc42-GTP around the division site during T1.…”
Section: Dynamics Of Cdc42 Polarization In Haploid Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast genome encodes 11 proteins with Rho-GAP domains. Genetic analyses suggested that three of these (Bem3p, Rga1p, and Rga2p) might be Cdc42p-specific and that their GAP domains catalyze GTP hydrolysis by Cdc42p in vitro (Bender and Pringle 1991;Zheng et al 1993Zheng et al , 1994Stevenson et al 1995;Chen et al 1996;Gladfelter et al 2002;Smith et al 2002). A fourth Rho-GAP (Bem2p) with genetic links to Cdc42p was initially thought to be selective for Rho1p (Zheng et al 1993), but was later shown to act on Cdc42p as well, at least in vitro (Marquitz et al 2002).…”
Section: Polarity Establishment In G1mentioning
confidence: 99%
“…Among the known upstream components, members of the Rho family of the small G proteins, such as Cdc42, have been identified as important modulators of MAPK cascades in S. cerevisiae (1). Whereas Cdc24 is believed to be the sole GEF for Cdc42 (1,14), three proteins have been proposed to be GAPs for Cdc42: Bem3, which has been shown to have GAP activity against Cdc42 in vitro (15, 16), Rga1/Dbm1 (17,18), and Rga2, which is identified by its homology to Rga1 (1).…”
mentioning
confidence: 99%